Household Preference Heterogeneity for Organic and Fairtrade Yellow Chilli in Lima, Peru [Resumen] - García Yi, Jaqueline (2011)
Certifying agricultural goods as organic and Fairtrade opens up two niche markets with potential benefits for both the environment and farmers in developing countries. Those certifications are expanding among farmers with access to external markets, but not among marginal farmers supplying internal markets in Peru. Those latter farmers state that national consumers are not willing to pay differential prices for certified products. In this research, we used a choice experiment to evaluate household marginal willingness to pay (mWTP) for three Organic and Fairtrade certification attributes: environmental protection, product without pesticides, and improvement in the quality of life of farmers. Yellow chilli was used as case study, because it is widely used for food preparation in Lima, Peru.